The Enhancement of Polysulfides Adsorption for Stable Lithium‐Sulfur Batteries Cathode Enabled by N‐Doped Wrinkled Graphene Using Solvothermal Method. Issue 35 (18th December 2017) - Yang, Rong; Li, Lan; Chen, Dan; Chen, Liping; Ren, Bing; Yan, Yinglin; Xu, Yunhua
Abstract: Lithium‐sulfur (Li−S) batteries have become a promising candidate in battery field recently due to their high theoretical energy density. However, the achievable energy density in the reality is much lower than the theoretical value for the reason that the sulfur is easily lost from active substances to the electrolyte. The main purpose of the present study has been intended to relieve this loss of sulfur, in which the nitrogen‐doped wrinkled graphene (NRGO) with nitrogen doping level of 7.63 wt% was thereby prepared by solvothermal method with urea as both nitrogen source and reducer. XPS reveals that pyrrolic‐N, pyridinic‐N and graphitic‐N were existed in NRGO and micro‐nano cavities were shown in the SEM morphology. The nano‐sulfur was in situ deposited on NRGO at low temperature to obtain nitrogen doped wrinkled graphene/sulfur composites (NRGO/S). The initial discharge capacity and columbic efficiency of NRGO/S composites are 1464.6 mA⋅h⋅g −1 and 96.3%, respectively, presenting a high reversible capacity comparing to reduced graphene oxide/sulfur composites (RGO/S). This can be explained by the pyridinic‐N and micro‐nano cavities within the present study, which are acting as favorable adsorption sites for polysulfides. It thereafter facilitates to depress the soluble polysulfides diffusion and further promotes the cycle ability of Li−S batteries. Abstract : The nano‐sulfur was in situ deposited on nitrogen‐doped wrinkled graphene prepared by solvothermal method with urea as both nitrogen source and reducer. The initial discharge capacity and columbic efficiency of the composites are 1464.6 mA⋅h⋅g −1 and 96.3%, respectively, presenting a high reversible capacity. This can be explained by the pyridinic‐N and micro‐nano cavities, which are acting as favorable adsorption sites for polysulfides. It thereafter facilitates to depress the soluble polysulfides diffusion and further promote the cycle ability.